FORMATION OF THE WORLDVIEW OF ELEMENTARY SCHOOL STUDENTS BASED ON THE WORKS OF EASTERN THINKERS - Tahirova Madinabonu Umidjon kizi (Galaxy International Interdisciplinary Research Journal, 2024)
This study investigates the formation of the worldview of elementary school students through exposure to the works of Eastern thinkers. Drawing from the rich philosophical traditions of the East, including but not limited to Confucianism, Taoism, and Buddhism, the research examines how concepts and teachings from these traditions influence the perspectives and beliefs of young learners. Through qualitative analysis of classroom interactions, assignments, and reflections, the study explores the impact of Eastern philosophical ideas on students’ understanding of self, society, and the world around them. The findings shed light on the potential of integrating Eastern philosophies into elementary education to foster holistic development and cultural awareness among students.